4H-SiC Ultraviolet Avalanche Photodiodes With Small Gain Slope and Enhanced Fill Factor - Sen Yang; Dong Zhou; Weizong Xu; Xiaolong Cai; Hai Lu; Dunjun Chen; Fangfang Ren; Rong Zhang; Youdou Zheng (IEEE Photonics Journal, 2017)
In this paper, 4H-SiC separated absorption charge and multiplication ultraviolet avalanche photodiodes (APDs) with small gain-voltage slope and enhanced fill factor are designed and fabricated. As a special reach-through structure, the absorption layer of the APD is fully depleted at breakdown voltage, which can share a considerable portion of reverse bias. As a result, the sensitivity of electric field within the multiplication layer as a function of overbias is reduced, leading to a small gain slope. Given the fact that the impact ionization coefficient of holes is less sensitive to electric field variation than that of electrons, the APD is also designed to be a hole-initiated ionization type, which can further reduce the gain slope. Meanwhile, three different top-electrode geometric patterns of SiC APDs are designed, and their impact on APD performance is investigated for the first time. Severe current crowding effect is observed in the forward current–voltage (I–V) characteristics of the APD with a traditional dot top-electrode, indicating inefficient current spreading across the top contact layer due to nonnegligible lateral resistance. In contrast, the forward I–V characteristics and photo-current at the avalanche regime of the APDs with optimized branch-shaped top-electrodes are apparently improved, owing to the improvement of electric field distribution and avalanche multiplication uniformity across the device active area. Furthermore, photon count rate increases by two to four times with larger voltage pulse height, suggesting enhanced effective avalanche multiplication area and fill factor.